The Application of Literary Theories in Literary Texts - Sandy Ferianda (Lire Journal)
This research mainly focused on discovering the application of literary theory in literary texts. Literary theories and literary texts were the same as two sides of a coin. They could not be separated or segregated. In addition, they both also helped people or the readers understand the application of them. However, even though literary theory and literary texts were interrelated or interconnected, they both shared different concept. Literary theory referred to on this basis, a set of assumptions or principles in which they could be used to explain, criticize, and interpret particular aspects, situations, or conditions in literary texts. Whereas, literary text, to some extent, referred to a created story in which it was based on people’s experience such as novels, poems, and many others.